Petrology mineralogy and geochemistry of rocks in the ZA-borehole onshore Zululand Basin : rock evaluation for CO2 sequestration - Altermann, Wladyslaw, 1954- (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2017.